Electro-optical system analysis and design : a radiometry perspective - Willers, Cornelius J. (SPIE Press, 2013)
The field of radiometry can be dangerous territory to the uninitiated, faced with the risk of errors and pitfalls. The concepts and tools explored in this book empower readers to comprehensively analyze, design, and optimize real-world systems. This book builds on the foundation of solid theoretical understanding, and strives to provide insight into hidden subtleties in radiometric analysis. Atmospheric effects provide opportunity for a particularly rich set of intriguing observations. The term 'radiometry' is used in its wider context to specifically cover the calculation of flux. This wider definition is commonly used by practitioners in the field to cover all forms of manipulation, including creation, measurement, calculation, modeling, and simulation of optical flux. Two concurrent themes frame the discussion: fragmenting a complex problem into simple building blocks and then designing complex systems from smaller elements. Analysis and design, as a creative synthesis of something new, cannot be easily taught other than by example; for this purpose, several case studies are presented. This book also provides a number of problems, some with solutions demonstrated in Matlab and the Python pyradi toolkit.
"SPIE Digital Library."--Website.
Keywords: Electrooptics.; Optical measurements.; Electrooptical devices -- Design and construction.; elektronické knihy; electronic books